-6+2n=3n-(6+5)

Simple and best practice solution for -6+2n=3n-(6+5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6+2n=3n-(6+5) equation:


Simplifying
-6 + 2n = 3n + -1(6 + 5)

Combine like terms: 6 + 5 = 11
-6 + 2n = 3n + -1(11)

Multiply -1 * 11
-6 + 2n = 3n + -11

Reorder the terms:
-6 + 2n = -11 + 3n

Solving
-6 + 2n = -11 + 3n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-3n' to each side of the equation.
-6 + 2n + -3n = -11 + 3n + -3n

Combine like terms: 2n + -3n = -1n
-6 + -1n = -11 + 3n + -3n

Combine like terms: 3n + -3n = 0
-6 + -1n = -11 + 0
-6 + -1n = -11

Add '6' to each side of the equation.
-6 + 6 + -1n = -11 + 6

Combine like terms: -6 + 6 = 0
0 + -1n = -11 + 6
-1n = -11 + 6

Combine like terms: -11 + 6 = -5
-1n = -5

Divide each side by '-1'.
n = 5

Simplifying
n = 5

See similar equations:

| m-13.2=5.9 | | B^2-10b+16=0 | | y-7.5=4.9 | | 8x-(7x+4)=2 | | 4+x+6=24 | | x^3-9x^2+14=0 | | 12r^2-25r+12= | | x=5.875+-0.4107142857y | | 8+4+6=8+6+4 | | 5.60x+2.30y=32.9 | | 4d^2+24d+36= | | x(x+10)=3(5x-2) | | 2x+20=9x-64 | | 5.60x+2.30x=32.9 | | 2x+20=4x+2 | | 8+4c= | | 7x^2=5x | | 85-4x=10+15 | | 2+12x+32=0 | | 8x(7x+4)=2 | | 10x+2y=-12 | | 2x^2=-x^2-5x-1 | | 4y=20x-12 | | (x-8)(x+11)=0 | | H=2y+8 | | 3x^2=-15x | | -4(x+2)+8=2(x-1)-7x+15 | | 242=0.5(4x^2) | | 1-2(x+1)=7x-1 | | x=5y+2a | | h^2-144= | | 13-3a=8 |

Equations solver categories